Dedicated non-destructive devices for food quality measurement: A review. (August 2018) - Abasi, Sadjad; Minaei, Saeid; Jamshidi, Bahareh; Fathi, Davood
Abstract: The quality of agricultural products is of high importance in terms of consumer interest, determining market acceptance, and thus, directly affects storage and post-harvest processing operations. Quality measurement of fruits, vegetables and food products is at the center of attention by the food industry. Non-destructive measurements of quality parameters have been conducted on many agricultural products and have proved to be rapid and accurate in estimating the quality factors involved. While, non-destructive methods are very useful for quality testing, the recent interest by consumers, researchers, and the food industry in the application of new portable and/or handheld non-destructive devices for quality assessment of agricultural products has added a new dimension to the issue. Because these devices are small-sized, low-cost, low-weight, and easy to use, they can be utilized by farmers, quality inspectors, and even consumers. Thus, researchers have focused on developing portable non-destructive devices for a variety of food items. This review, examines the latest reports on the design and development of dedicated non-destructive portable and/or handheld devices for quality monitoring of agricultural products. Highlights: Demands for dedicated devices for food quality sensing have been increased. Non-destructive methods have high capability to use for development such devices. Low-cost, low-weight, user-friendly and rapid inspection are of high importance. Different methods have been applied to development of dedicated non-destructive devices. Advanced techniques will be introduced to improve performance of these devices.